Real-time teaching of industrial robots Using a synchronised stereoscopic vision system - António Paulo Moreira (2009)
In this paper a method to control and teach industrial robots in real-time by human demonstration is presented. This system uses high-intensity visual markers that make it sufficiently robust for industrial environments not requiring special lighting. An automated camera calibration method was implemented which enables any non-skilled user a quick and easy configuration of the system. The teaching of the robot is achieved by recording the detected points and replaying them to the manipulator, therefore this is a "teaching-by-showing" method. This system can work with any kind of industrial manipulator capable of receiving remote positioning commands.